Serum uric acid in smokers - Bassam E Hanna; Luma M Tohala; Jamal M Hamed (University of Mosul, 2010)
Objectives: To demonstrate the possible effect of smoking on serum uric acid level. Methods: The study was conducted during the period from March to June 2008 in Mosul city as a case control study. Participants: Subjects enrolled in this study were divided into two groups; nonsmokers and smokers composed of 47 and 40 apparently healthy male volunteers respectively with the same dietary habit, no pastmedical history of diabetes mellitus , hyperuricemia and gout , renal, lung or heart diseases or drug history affecting uric acid level. Smoker group is subdivided into heavy , moderate and mild smokers. Fasting blood and random urine samples were obtained from both groups for measurement of uric acid and creatinine. Calculation of both urine uric acid/urine creatinine ratio and fraction excretion of uric acid were done. Results: No significant differences in the age , serum creatinine , spot urine uric acid/urine creatinine ratio and fraction excretion of uric acid between two groups where as serum uric acid was significantly lower in smokers. In smokers there are significant negative correlations of the average number of cigarette smoked/day and the duration of smoking with serum uric acid level. Heavy , moderate and mild smokers showed no significant differences in the age , urine uric acid/urine creatinine ratio , fraction excretion of uric acid , serum creatinine and serum uric acid except a significant lower serum uric acid value in the heavy smoker compared with moderate and mild smokers . Conclusion: The significant low serum uric acid level in smokers is due to the reduction of endogenous production as a result of chronic exposure to cigarette smoke that is a significant source of oxidative stress and as this reduction is proportionate with the duration and number of cigarette smoked/day and as low uric acid predispose to cardiovascular diseases as proved by other studies, therefore, its recommended for smokers to stop or reduce smoking with the use of serum uric acid as a routine test for follow-up as it is inexpensive , simple to reflect antioxidant level.